Chaucer and the country of the stars : poetic uses of astrological imagery - Wood, Chauncey (Princeton legacy library., 1970)
Professor Wood examines in detail the astrological references in The Canterbury Tales, Troilus and Criseyde, and The Complaint of Mars, using mediaeval source materials not only to elucidate the technicalities of the imagery but also to analyze its poetic function. Originally published in 1970. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable p.